2008
DOI: 10.1016/j.bpc.2008.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly in aqueous solution of a modified amyloid beta peptide fragment

Abstract: The self assembly in aqueous solution of a modified amyloid beta peptide fragment is studied. We focus on sequence , KLVFF, extended by two alanines at the N terminus to give AAKLVFF. Self-assembly into twisted ribbon fibrils is observed, as confirmed by transmission electron microscopy (TEM). Dynamic light scattering reveals the semi-flexible nature of the AAKLVFF fibrils, while polarized optical microscopy shows that the peptide fibrils crystallize after an aqueous solution of AAKLVFF is matured over 5 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
69
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 24 publications
9
69
0
1
Order By: Relevance
“…This 225 nm minimum is red-shifted compared to the characteristic β-sheet minimum near 217 nm (ref. 55), yet similar spectra were previously reported in other supramolecular β-sheet peptide assemblies5657. Lastly, ThT binding further supported the formation of β-sheets by the 9-mer (Fig.…”
Section: Resultssupporting
confidence: 87%
“…This 225 nm minimum is red-shifted compared to the characteristic β-sheet minimum near 217 nm (ref. 55), yet similar spectra were previously reported in other supramolecular β-sheet peptide assemblies5657. Lastly, ThT binding further supported the formation of β-sheets by the 9-mer (Fig.…”
Section: Resultssupporting
confidence: 87%
“…The FT-IR spectrum of Boc-II-OMe ( Figure 6A) shows bands at 1625 and 1682 cm À1 , suggesting the presence of antiparallel b-sheet conformation [48][49][50][51][52][53][54][55]. An additional band at 1648 cm À1 suggests the presence of unordered structure [48,55].…”
Section: Attenuated Total Internal Reflection Ft-ir Spectroscopymentioning
confidence: 99%
“…The values of 4.8 Å and 12.6 Å are similar to those seen in fibrillar protein aggregates, such as Aβ plaques. 13 Previous work has indicated that the 4.8 Å peak likely belongs to the hydrogen bonding distance in the β-sheet, whereas the 12.6 Å peak is attributed to the spacing between β-sheets. 7 In contrast, PA 2 showed no significant diffraction in either the freshly dissolved solution or any of the aged solutions (Figure S6).…”
mentioning
confidence: 96%
“…Efforts to find the minimum peptide segment necessary for Aβ protein fibrillization have yielded the KLVFF sequence. 7,13,14 Phenylalanine residues are of particular importance in the aggregation of Aβ. 15 In this context, Gazit et al demonstrated that only a dimer of phenylalanine is needed to assemble into nanotubes as a result of the π-π stacking.…”
mentioning
confidence: 99%